2016
DOI: 10.1021/acs.organomet.6b00297
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Defined Isocyano Analogue of HCo(CO)4. 1: Synthesis, Decomposition, and Catalytic 1,1-Hydrogenation of Isocyanides

Abstract: Reported here is the synthesis and characterization of the tetrakis­(m-terphenyl isocyanide)cobalt hydride HCo­(CNArMes2)4 (1; ArMes2 = 2,6-(2,4,6-Me3C6H2)2C6H3). Monohydride 1 serves as a well-defined isocyano analogue of the tetracarbonyl hydride HCo­(CO)4. While tetrakis-phosphine analogues of HCo­(CO)4 have been reported previously, these compounds have failed to exhibit a reactivity profile that can be compared and contrasted with HCo­(CO)4 in a systematic fashion. Herein, HCo­(CNArMes2)4 (1) is shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 118 publications
4
54
0
Order By: Relevance
“…The only other such imine structurer eported, also with ab ulky substituent on nitrogen, CH 2 =NAr (Ar = 2,6-(2,4,6-Me 3 C 6 H 2 ) 2 C 6 H 3 ), also exhibits as imilar NH 2 group orthogonal to the aryl group with as imilar CÀN methylene bond length of 1.247 . [15] In both the reported imine and ours, the methylene protons can be noted by 1 HNMR spectroscopy as ap air of doublets, for 4 at 6.12 ( 1 J HH = 18 Hz) and 7.13 ppm ( 1 J HH = 12 Hz), respectively.I mine 4,u nlike the previously reported example, is av ery thermally and oxida-tively stable materiala nd its possible chemicalr eactivity is currently under investigation.…”
Section: Imine Formationsupporting
confidence: 56%
“…The only other such imine structurer eported, also with ab ulky substituent on nitrogen, CH 2 =NAr (Ar = 2,6-(2,4,6-Me 3 C 6 H 2 ) 2 C 6 H 3 ), also exhibits as imilar NH 2 group orthogonal to the aryl group with as imilar CÀN methylene bond length of 1.247 . [15] In both the reported imine and ours, the methylene protons can be noted by 1 HNMR spectroscopy as ap air of doublets, for 4 at 6.12 ( 1 J HH = 18 Hz) and 7.13 ppm ( 1 J HH = 12 Hz), respectively.I mine 4,u nlike the previously reported example, is av ery thermally and oxida-tively stable materiala nd its possible chemicalr eactivity is currently under investigation.…”
Section: Imine Formationsupporting
confidence: 56%
“…But unlike HTa(PF 3 ) 6 which is fairly robust, no evidence for the isocyanide hydride was obtained. Isocyanide metal hydrides are rare species and Figueroa and co‐workers recently reported [HFe(CNAr′) 4 ] −[31a] and [HCo(CNAr′) 4 ] …”
Section: Figurementioning
confidence: 99%
“…Earlier studies showed that these pentakis and tetrakis cobalt(II) complexes react with amines to undergo reduction to their 4 ] in the À1, 0, and +1 oxidation states were synthesized a few years back [29] using m-terphenyl isocyanide as the stabilizing ligand. The same ligand was later employed in the synthesis of the isocyano counterpart of HCo(CO) 4 followed by a study of its decomposition and catalytic hydrogenation [30]. Figueroa and co-workers [31] most recently synthesized some isocyanide palladium(0) complexes as catalysts for the SuzukiMiyaura cross-coupling of aryl bromides and arylboronic acids.…”
Section: Introductionmentioning
confidence: 99%